Manajemen Pembelajaran Pendidikan Agama Islam SDN-3 Telangkah Desa Hampalit Kabupaten Katingan - Muhammad Arni (Jurnal Hadratul Madaniyah, 2017)
Obstacles faced Islamic primary school teachers of the country Telangkah Kereng Pangi 3 in carrying out education of Islam such as the lack of teachers in particular Islamic religious teachers at that school, which amounted to two teachers from 26 teachers with class as much as 18 spaces. In addition teachers also can not combine class with other classes due to the number of Muslim students in a single classroom almost 35-40 people especially students in class v. allocation of time set by the school are always placed at the last hour, and infrastructure is still lacking as to the absence of small mosque or place of practice. and almost 85 teachers at that school non-muslim religion. The efforts made by the Islamic religious teachers of the primary school Telangkah-3 Country Kereng Pangi still not in accordance with the theory, due to the many limitations of the teacher's knowledge. Islamic religious teachers only implement learning just as much as the other teachers that is in the process of teaching and learning for example conveying material, explain, give the task either orally or in writing, and faqs..